GENETIC AND SEASONAL VARIATION IN COCONUT PRODUCTION - K. SATYABALAN (International Coconut Community Journal, 1998)
Variation in the yield of nuts in the coconut palms due to genetic differences of the palms and seasonal effects in the West Coast Tall cultivarpalms grown in a well‑maintained estate in Kerala on the west coast of India was studied every month continuously for a period offive years. The varying yield capacity and bearing tendency noticed in the palms may be attributed to the genetic differences between the palms. The marked fluctuations in the yield of palms classified as high yielders‑ those which yield 80 nuts and above per palm per year and low yielders ‑ those which yield 10 nuts and above per palm per year, do not follow a specific trend as in the case of seasonal variations. The yield of nuts in 66 palms in the estate which comprised of all the three yield groups during the different seasons of the year identified in Kerala as Hot Weather Season during the months of March, April and May, Southwest Monsoon Season during the months of June, July and August, Northeast Monsoon Season during the months of September, October and November and Cold Weather Season during the months of December, January and February showed that high yields of the palms in all the three yield groups were obtained mainly during the Hot Weather Season of the year. This pattern of production due to seasonal influence is seen to persist year afteryear irrespective of the magnitude of the yield obtained, with minor variations. This is attributed to the cyclic influence of varying seasons in a year on the different critical stages of initiation and development of the inflorescence which takes about 32 months from its initiation to open ing and during the development of the nut which takes about 12 months to develop from a fertilized female flower. The palms in the high yield group exhibit only slight variation and maintain their high yields than those in the medium and low yield groups. Data on the yield of palms during a period of five years indicate that those palms which continuously yield 80 nuts and above per year regularly for at least four years turn out to be regular bearers and high yielders. They should, as far as possible be selected as mother palms for propagation.